2015
DOI: 10.4314/mejs.v7i1.117233
|View full text |Cite
|
Sign up to set email alerts
|

Food and Feeding Habits of the Common Carp (<i>Cyprinus carpio</i> L. 1758) (Pisces: Cyprinidae) in Lake Koka, Ethiopia

Abstract: Feeding habits of Cyprinus carpio was studied in Lake Koka, Ethiopia, in April and May (dry months) and July and August (wet months), 2011. The objective of the study was to identify the diet composition, seasonal variation in diet and ontogenetic dietary shift. Gut contents of 435 fish were analyzed using frequency of occurrence and volumetric analysis. In frequency of occurrence method the number of gut samples was expressed as a percentage of all non-empty stomachs examined while in volumetric method the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…O. aureus fed mainly on macrophytes, algae and diatoms, whereas C. zillii consumed mainly macrophytes and algae. These research findings are similar to the previous study on O. aureus conducted by Dadebo et al [43] in Lake Koka, Ethiopia, Khalifa [59] in the Tigris river, Iraq and Mohamed and Al-Wan [60] in the Garmat Ali river. Also, the previous studies stated that the C. zillii was herbivores, such as Wahab [34] in Tigris river, Iraq, Onyeche et al [61] in the Anwai stream, Niger, Dadebo et al [43] in Lake Koka, Ethiopia, Adams [62] in the Tiga dam, Nigeria and Mohamed and Al-Wan [60] in the Garmat Ali river.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…O. aureus fed mainly on macrophytes, algae and diatoms, whereas C. zillii consumed mainly macrophytes and algae. These research findings are similar to the previous study on O. aureus conducted by Dadebo et al [43] in Lake Koka, Ethiopia, Khalifa [59] in the Tigris river, Iraq and Mohamed and Al-Wan [60] in the Garmat Ali river. Also, the previous studies stated that the C. zillii was herbivores, such as Wahab [34] in Tigris river, Iraq, Onyeche et al [61] in the Anwai stream, Niger, Dadebo et al [43] in Lake Koka, Ethiopia, Adams [62] in the Tiga dam, Nigeria and Mohamed and Al-Wan [60] in the Garmat Ali river.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies mentioned that C. auratus was herbivorous species [33,37,38]. The omnivorous feeding habit for C. carpio has been observed by several authors, like Saud [31] in the Qarmat Ali River, Al-Shamma'a et al [39] in the Haditha Dam, Saikia and Das [40] in Indian lakes, Hussain et al [41] in southern marshes, Ali et al [42] in Hirfanli Dam, Turkey, Mohamed and Hussain [37] in East Hammar marsh and Dadebo et al [43] in Lake Koka, Ethiopia. Some previous studies indicated that C. carpio was carnivorous species [44,45].…”
Section: Discussionmentioning
confidence: 85%
“…In nearby Lake Koka, Dadebo et al. (2015) have reported that macrophytes and detritus are the main diets of common carp. However, there was no study on food and feeding habits of common carp and also a dietary overlap of common carp and Nile tilapia in Lake Ziway.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture, the lake supports the fishing industry each year with 625 tons of fish harvest, while Nile tilapia contributes about 59% of the total fish landings (Dadebo, Eyayu, Sorsa, & Tilahun, 2015).…”
mentioning
confidence: 99%